2021
DOI: 10.47162/rjme.62.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic lymphohistiocytosis in a child with human immunodeficiency virus infection – a case report

Abstract: Introduction: Hemophagocytic lymphohistiocytosis (HLH) is a rare condition and furthermore human immunodeficiency virus (HIV)-associated HLH is rarely reported in the literature. The most frequent presentation of secondary HLH is in association with infections, malignancies or drugs. In HIV-positive patients, the viral infection itself or the antiretroviral therapy (ART) could trigger HLH. Case presentation: A 14-year-old boy was admitted for persistent diarrhea, severe weight loss and chest burns. Laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Another retrospective study on nine adult UK subjects (with mean age of 73 years) with SARS (due to coronavirus as cause of death was published in 2020 [81]. Post-mortem analysis showed that 33% of studied patients had an adrenal microinfarction, while thrombotic events were confirmed in 89% of cases, mostly at pulmonary level, in association with other three major HP elements including diffuse alveolar damage (which was confirmed in all the studied individuals), immune anomalies like lymphocyte depletion [mostly cluster of differentiation (CD)-positive T-cells], as well as hemophagocytes [as otherwise seen in other severe infections like human immunodeficiency virus (HIV) infection] [81,82]. If recognized, AI-related adrenal insufficiency requires intravenous Hydrocortisone, followed by lifetime oral Hydrocortisone and Fludrocortisone [83].…”
Section: Clinical Elementsmentioning
confidence: 79%
“…Another retrospective study on nine adult UK subjects (with mean age of 73 years) with SARS (due to coronavirus as cause of death was published in 2020 [81]. Post-mortem analysis showed that 33% of studied patients had an adrenal microinfarction, while thrombotic events were confirmed in 89% of cases, mostly at pulmonary level, in association with other three major HP elements including diffuse alveolar damage (which was confirmed in all the studied individuals), immune anomalies like lymphocyte depletion [mostly cluster of differentiation (CD)-positive T-cells], as well as hemophagocytes [as otherwise seen in other severe infections like human immunodeficiency virus (HIV) infection] [81,82]. If recognized, AI-related adrenal insufficiency requires intravenous Hydrocortisone, followed by lifetime oral Hydrocortisone and Fludrocortisone [83].…”
Section: Clinical Elementsmentioning
confidence: 79%
“…Primary HLH is associated with genetic mutations that alter the cytotoxic activity of NK cells and CD8 lymphocytes. These cells accumulate in organs such as the spleen and bone marrow, where they attack erythrocytes, leukocytes, and platelets [ 2 ]. Therefore, the affliction occurs in the first years of life.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the affliction occurs in the first years of life. Conversely, secondary HLH is triggered by infections caused by the Epstein–Barr virus (EBV), cytomegalovirus (CMV), human herpesvirus-8 (HHV-8), Histoplasma capsulatum , and, less frequently, the human immunodeficiency virus (HIV), as well as malignant neoplasms (lymphomas in greater frequency), autoimmune or autoinflammatory diseases, and drugs such as antiretroviral therapy (ART) [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations